Torture and torturous violence: transcending definitional of torture - Canning, Victoria (Bristol University Press, 2023)
"There is growing acknowledgement that torture is too narrowly defined in law, and that psychological and/or sexualised violence against women is not adequately recognized as torture. Clearly conceptualising torturous violence, this book offers scholars and practitioners critical reflections on how torture is defined and the implications that narrow definitions may have on survivors. Drawing on over a decade of research and interviews with psychologists, practitioners and women seeking asylum, it sets out the implications of the social silencing of torture, and torturous violence specifically. It invites us to consider alternative ways to understand and address the impacts of physical, sexualized and psychological abuses"--